Laser cladding-based aluminide modified coating and preparation method thereof

By introducing Pd and Zr into the aluminide coating and using laser cladding process to form an aluminide modified coating, the problem of insufficient oxidation resistance and thermal corrosion resistance of the existing coating under high power and complex operating conditions is solved, and better oxidation resistance and production efficiency are achieved.

CN119753669APending Publication Date: 2025-04-04HUANENG HUNAN YUEYANG POWER GENERATION CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411889543.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the long-term service and high-power operation of existing aluminide coatings, the reduced Al content leads to a deterioration of oxidation resistance, and lacks anti-oxidation and thermal corrosion resistance under complex working conditions.

Method used

Using aluminide modified coating preparation method based on laser cladding, a coating with excellent oxidation resistance is formed by introducing modified elements Pd and Zr into the solid-phase cladding powder, combined with a laser cladding process.

Benefits of technology

By introducing Pd and Zr, external diffusion of elements and internal diffusion of oxygen atoms are hindered, Al content is maintained and oxidative behavior is delayed, and the antioxidant properties and thermal corrosion resistance of the coating are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753669A_ABST
    Figure CN119753669A_ABST
Patent Text Reader

Abstract

The invention discloses an aluminide modified coating based on laser cladding and a preparation method of the aluminide modified coating. After the surface of a workpiece to be plated is cleaned and preheated, cladding slurry is uniformly sprayed to the surface of the workpiece, natural air drying and medium-temperature curing are conducted, and finally the aluminide cladding coating is obtained through laser cladding; wherein the solid-phase cladding powder comprises the following components in percentage by mass: 60%-80% of FeAl, 10%-30% of Al, 3%-6% of Pd, 3%-6% of Zr and 2%-7% of NH4Cl. According to the laser-cladding aluminide coating and the preparation method thereof, a prepared infiltrated layer is uniform in organization structure, moderate in thickness, sufficient in Al atom diffusion, good in metallurgical bonding with a base body, not prone to falling off and suitable for austenitic steel and high-temperature alloy parts used for workpieces with the large length-diameter ratio and various complex shapes such as large boilers and oil and gas field conveying pipelines; and the method has excellent industrial batch production benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material surface alloying and coating preparation, and specifically relates to an aluminide modified coating based on laser cladding and a preparation method thereof. Background Art

[0002] In the thermal power generation industry, pipe blockage and burst accidents caused by oxide scale problems on the inner wall of flow components account for more than 50% of boiler non-shutdown accidents, resulting in an increase of more than 20% in the operating and material costs of the units; the corrosion of flow components with large aspect ratios has become an industry common problem and technical pain point that restricts the safe production and operation of the entire energy equipment.

[0003] Studies have shown that high-temperature coatings have obvious effects in solving the problems of component oxidation corrosion, wear, and high-temperature ablation, and are widely used in various industrial boiler systems. In response to the oxidation and corrosion problems of boiler pipes, the aluminide coating developed by Xi'an Thermal Engineering Research Institute has shown superior antioxidant ability on the flow-through components of energy equipment with large aspect ratios. However, with the extension of service time and the increase in unit power, the reduction in Al content in the coating will inevitably affect the antioxidant performance of the coating. In addition, the antioxidant and heat-resistant capabilities of a single aluminide coating under complex working conditions such as thermal corrosion, oxidation, and flue gas need to be improved. Therefore, it is necessary to develop a new type of antioxidant and heat-resistant coating preparation technology and process with excellent comprehensive performance, suitable for various complex-shaped workpieces with large aspect ratios. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing an aluminide modified coating based on laser cladding.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:

[0008] The solid phase cladding raw materials are ball milled and mixed to obtain solid phase cladding powder;

[0009] The solid phase cladding powder and the liquid phase binder are stirred and ball-milled to obtain a cladding slurry;

[0010] The cladding slurry is evenly sprayed onto the surface of the preheated workpiece to form a prefabricated slurry layer;

[0011] The dried and solidified workpiece is placed in an inert atmosphere for laser cladding treatment, cooled after treatment, and the residue is cleaned to form an aluminide modified coating on the surface of the workpiece;

[0012] Wherein, the solid phase cladding powder comprises, in terms of mass percentage, 60-80% FeAl, 10-30% Al, 3-6% Pd, 3-6% Zr and 2-7% NH4Cl.

[0013] As a preferred solution of the method for preparing the aluminide modified coating based on laser cladding of the present invention, the mixed ball milling speed of the solid phase cladding raw material is 350 to 400 rpm and the time is 12 to 24 hours.

[0014] As a preferred solution of the method for preparing the aluminide modified coating based on laser cladding of the present invention, the liquid phase binder is ethyl acetate, and the amount used is 10wt% to 30wt% of the solid phase cladding powder.

[0015] As a preferred embodiment of the method for preparing the aluminide modified coating based on laser cladding of the present invention, the stirring time of the solid-phase cladding powder and the liquid-phase binder is 2 to 4 hours, the ball milling speed is 350 to 400 rpm, and the time is 8 to 12 hours.

[0016] As a preferred solution of the method for preparing the aluminide modified coating based on laser cladding of the present invention, the preheating treatment is medium frequency preheating at 200-250° C. for 30-60 minutes.

[0017] As a preferred solution of the method for preparing the aluminide modified coating based on laser cladding of the present invention, the thickness of the prefabricated slurry layer is 1 to 5 mm, and the coating coverage is not less than 98%.

[0018] As a preferred solution of the method for preparing the aluminide modified coating based on laser cladding of the present invention, wherein: the drying is carried out by natural air drying, and the drying time is 24 to 48 hours.

[0019] As a preferred solution of the method for preparing the aluminide modified coating based on laser cladding of the present invention, wherein: the curing is performed at 300 to 450° C. for 24 to 48 hours.

[0020] As a preferred scheme of the preparation method of the aluminide modified coating based on laser cladding described in the present invention, the cladding laser power of the laser cladding treatment is 2 to 2.8 KW, the scanning rate is 20 to 40 mm / s, the spot diameter is 3 to 5 mm, the workpiece rotation speed is 3 to 6 r / min, and the Ar gas flow rate is 15 to 20 L / min.

[0021] Another object of the present invention is to provide an aluminide modified coating based on laser cladding.

[0022] Beneficial effects of the present invention:

[0023] (1) The laser cladding aluminide modified coating provided by the present invention can hinder the external diffusion of elements, maintain the Al content in the FeAl phase, and optimize the antioxidant performance by introducing the modifying element Pd into the solid phase powder; the introduction of the modifying element Zr can hinder the internal diffusion of oxygen atoms and the external diffusion of aluminum atoms, and delay the occurrence of oxidation behavior.

[0024] (2) The present invention prepares the coating through an integrated laser cladding process production line. The process has concentrated heat, short action time, small thermal impact in the cladding zone, high coating production efficiency, controllable thickness, high process repeatability, and is extremely practical and universal. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0026] Figure 1 This is the cross-sectional morphology of the laser-clad aluminide modified coating prepared in Example 1 of the present invention.

[0027] Figure 2 This is a line scan diagram of the Al content in the infiltration layer of the sample prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0028] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0029] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0030] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0031] Unless otherwise specified, the raw materials used in the present invention are all commercially available in the art.

[0032] The method for measuring the coating thickness of the present invention is as follows:

[0033] The thickness of the diffusion layer was measured under a scanning electron microscope (SEM) (Zeiss-Sigma HD) and a backscattered HDBSD (Zeiss-Sigma HD).

[0034] The antioxidant performance of the sample of the present invention is obtained by placing the sample in a 650° C. steam environment for 500 hours and measuring the weight gain.

[0035] Example 1

[0036] This embodiment provides a method for preparing an aluminide modified coating based on laser cladding, specifically:

[0037] 1) Based on the mass percentage of the solid phase cladding raw materials, 60% FeAl, 30% Al, 3% Pd, 5% Zr and 2% NH4Cl were weighed, placed in a planetary ball mill at 400 rpm for 12 h, and passed through a 1000 mesh sieve to obtain a solid phase cladding powder;

[0038] Add ethyl acetate in an amount of 10% of the weight of the solid phase cladding powder, stir thoroughly for 4 hours, and then place in a planetary ball mill at 400 rpm for 12 hours to obtain a uniformly mixed slurry, which is the cladding slurry;

[0039] 2) Use a high-pressure water gun to clean the workpiece surface for 5 minutes, rinse it with alcohol or acetone, and preheat the workpiece at 250°C for 45 minutes;

[0040] Spray the cladding slurry onto the workpiece surface to form a prefabricated slurry layer with a thickness of 3 mm, and maintain the coating coverage rate not less than 98%;

[0041] 3) The workpiece with the prefabricated slurry layer was naturally air-dried for 48 hours and cured at 450°C for 48 hours. The cured workpiece was placed under Ar for laser cladding treatment with a laser power of 2.8 kW, a scanning rate of 40 mm / s, a spot diameter of 2 mm, a workpiece rotation speed of 5 r / min, and an Ar gas flow rate of 15 L / min. After completion, the workpiece was cooled to room temperature and the residue on the surface of the workpiece was washed with a high-pressure airflow to clean the residue, thereby forming an aluminide modified coating on the surface of the workpiece.

[0042] Figure 1 This is a cross-sectional morphology of the aluminide modified layer prepared in this embodiment. It can be seen that the coating has a uniform structure and a moderate thickness. Figure 2This is a line scan of the Al content in the infiltration layer of the sample prepared in this embodiment. It can be seen that the Al content decreases evenly from the infiltration layer to the matrix, indicating that the Al atoms are fully diffused, the infiltration layer and the matrix are well metallurgically bonded and not easy to fall off.

[0043] Example 2

[0044] The difference between this embodiment and embodiment 1 is that the laser cladding process conditions are adjusted, and the remaining steps are referred to embodiment 1 to obtain aluminide modified coatings under different laser cladding process conditions. The corresponding laser cladding process conditions and coating thicknesses are shown in Table 1.

[0045] Table 1 Coating thickness corresponding to different laser cladding process conditions

[0046]

[0047]

[0048] It can be seen from Table 1 that the thickness of the coatings obtained under different cladding process conditions is 0.25-1.41 mm, and the coatings obtained under the cladding process conditions of the present invention all have good anti-oxidation properties.

[0049] Example 3

[0050] 1) Based on the mass percentage of the solid phase cladding raw materials, 70% FeAl, 15% Al, 6% Pd, 3% Zr and 6% NH4Cl were weighed, placed in a planetary ball mill at 400 rpm for 12 h, and passed through a 1000 mesh sieve to obtain a solid phase cladding powder;

[0051] Add 30% ethyl acetate compared to the weight of the solid phase cladding powder, stir thoroughly for 4 hours, and then place in a planetary ball mill at 400 rpm for 12 hours to obtain a uniformly mixed slurry, which is the cladding slurry;

[0052] 2) Use a high-pressure water gun to clean the workpiece surface for 5 minutes, rinse it with alcohol or acetone, and preheat the workpiece at 200°C for 60 minutes;

[0053] Spray the cladding slurry onto the workpiece surface to form a prefabricated slurry layer with a thickness of 3 mm, and maintain the coating coverage rate not less than 98%;

[0054] 4) The workpiece with the prefabricated slurry layer was naturally air-dried for 24 hours and cured at 300°C for 48 hours. The cured workpiece was placed under Ar for laser cladding treatment with a laser power of 2 kW, a scanning rate of 20 mm / s, a spot diameter of 2 mm, a workpiece rotation speed of 5 r / min, and an Ar gas flow rate of 15 L / min. After completion, it was cooled to room temperature and the residue on the surface of the workpiece was washed with a high-pressure airflow to clean the residue, thereby forming an aluminide modified coating of this embodiment on the surface of the workpiece.

[0055] Example 4

[0056] 1) Based on the mass percentage of the solid phase cladding raw materials, 80% FeAl, 10% Al, 3% Pd, 3% Zr and 4% NH4Cl were weighed, placed in a planetary ball mill at 400 rpm for 24 hours, and passed through a 1000 mesh sieve to obtain a solid phase cladding powder;

[0057] Add ethyl acetate in an amount of 20% of the weight of the solid phase cladding powder, stir thoroughly for 4 hours, and then place in a planetary ball mill at 350 rpm for 8 hours to obtain a uniformly mixed slurry, which is the cladding slurry;

[0058] 2) Use a high-pressure water gun to clean the workpiece surface for 5 minutes, rinse it with alcohol or acetone, and preheat the workpiece at 200°C for 60 minutes;

[0059] Spray the cladding slurry onto the workpiece surface to form a prefabricated slurry layer with a thickness of 3 mm, and maintain the coating coverage rate not less than 98%;

[0060] 3) The workpiece with the prefabricated slurry layer was naturally air-dried for 24 hours and cured at 450°C for 48 hours. The cured workpiece was placed under Ar for laser cladding treatment with a laser power of 2.8 kW, a scanning rate of 40 mm / s, a spot diameter of 3 mm, a workpiece rotation speed of 2 r / min, and an Ar gas flow rate of 15 L / min. After completion, the workpiece was cooled to room temperature and the residue on the surface of the workpiece was washed with a high-pressure airflow to clean the residue, thereby forming an aluminide-modified coating of this embodiment on the surface of the workpiece.

[0061] Example 5

[0062] 1) Based on the mass percentage of the solid phase cladding raw materials, 70% FeAl, 12% Al, 6% Pd, 6% Zr and 6% NH4Cl were weighed and placed in a planetary ball mill at 400 rpm for 12 h, and passed through a 1000 mesh sieve to obtain a solid phase cladding powder;

[0063] Add ethyl acetate in an amount of 20% of the weight of the solid phase cladding powder, stir thoroughly for 2 hours, and then place in a planetary ball mill at 350 rpm for 12 hours to obtain a uniformly mixed slurry, which is the cladding slurry;

[0064] 2) Use a high-pressure water gun to clean the workpiece surface for 5 minutes, rinse it with alcohol or acetone, and preheat the workpiece at 200°C for 60 minutes;

[0065] Spray the cladding slurry onto the workpiece surface to form a prefabricated slurry layer with a thickness of 3 mm, and maintain the coating coverage rate not less than 98%;

[0066] 3) The workpiece with the prefabricated slurry layer was naturally air-dried for 24 hours and cured at 400°C for 48 hours. The cured workpiece was placed under Ar for laser cladding treatment with a laser power of 2.8KW, a scanning rate of 20mm / s, a spot diameter of 3mm, a workpiece rotation speed of 5r / min, and an Ar gas flow rate of 15L / min. After completion, it was cooled to room temperature and the residue on the surface of the workpiece was washed with a high-pressure airflow to clean the residue, thereby forming the aluminide modified coating of this embodiment on the surface of the workpiece.

[0067] Example 6

[0068] 1) Based on the mass percentage of the solid phase cladding raw materials, 70% FeAl, 15% Al, 5% Pd, 3% Zr and 7% NH4Cl were weighed and placed in a planetary ball mill at 400 rpm for 24 hours, and passed through a 1000 mesh sieve to obtain a solid phase cladding powder;

[0069] Add 30% ethyl acetate compared to the weight of the solid phase cladding powder, stir thoroughly for 2 hours, and then place in a planetary ball mill at 400 rpm for 12 hours to obtain a uniformly mixed slurry, which is the cladding slurry;

[0070] 2) Use a high-pressure water gun to clean the workpiece surface for 5 minutes, rinse it with alcohol or acetone, and preheat the workpiece at 250°C for 45 minutes;

[0071] Spray the cladding slurry onto the workpiece surface to form a prefabricated slurry layer with a thickness of 5 mm, and maintain the coating coverage rate not less than 98%;

[0072] 3) The workpiece with the prefabricated slurry layer was naturally air-dried for 24 hours and cured at 450°C for 48 hours. The cured workpiece was placed under Ar for laser cladding treatment with a laser power of 2 kW, a scanning rate of 30 mm / s, a spot diameter of 5 mm, a workpiece rotation speed of 5 r / min, and an Ar gas flow rate of 18 L / min. After completion, the workpiece was cooled to room temperature and the residue on the surface of the workpiece was washed with a high-pressure airflow to clean the residue, thereby forming an aluminide-modified coating of this embodiment on the surface of the workpiece.

[0073] Example 7

[0074] 1) Based on the mass percentage of the solid phase cladding raw materials, 60% FeAl, 30% Al, 3% Pd, 5% Zr and 2% NH4Cl were weighed and placed in a planetary ball mill at 400 rpm for 24 hours, and passed through a 1000 mesh sieve to obtain a solid phase cladding powder;

[0075] Add 30% ethyl acetate compared to the weight of the solid phase cladding powder, stir thoroughly for 4 hours, and then place in a planetary ball mill at 400 rpm for 12 hours to obtain a uniformly mixed slurry, which is the cladding slurry;

[0076] 2) Use a high-pressure water gun to clean the workpiece surface for 5 minutes, rinse it with alcohol or acetone, and preheat the workpiece at 250°C for 60 minutes;

[0077] Spray the cladding slurry onto the workpiece surface to form a prefabricated slurry layer with a thickness of 4 mm, and maintain the coating coverage rate not less than 98%;

[0078] 3) The workpiece with the prefabricated slurry layer was naturally air-dried for 36 hours and cured at 450°C for 48 hours. The cured workpiece was placed under Ar for laser cladding treatment with a laser power of 2.8 kW, a scanning rate of 40 mm / s, a spot diameter of 5 mm, a workpiece rotation speed of 4 r / min, and an Ar gas flow rate of 20 L / min. After completion, the workpiece was cooled to room temperature and the residue on the surface of the workpiece was washed with a high-pressure airflow to clean the residue, thereby forming an aluminide-modified coating of this embodiment on the surface of the workpiece.

[0079] Example 8

[0080] 1) Based on the mass percentage of the solid phase cladding raw materials, 60% FeAl, 30% Al, 3% Pd, 5% Zr and 2% NH4Cl were weighed and placed in a planetary ball mill at 350 rpm for 24 hours, and passed through a 1000 mesh sieve to obtain a solid phase cladding powder;

[0081] Add ethyl acetate in an amount of 20% of the weight of the solid phase cladding powder, stir thoroughly for 4 hours, and then place in a planetary ball mill at 400 rpm for 8 hours to obtain a uniformly mixed slurry, which is the cladding slurry;

[0082] 2) Use a high-pressure water gun to clean the workpiece surface for 5 minutes, rinse it with alcohol or acetone, and preheat the workpiece at 250°C for 60 minutes;

[0083] Spray the cladding slurry onto the workpiece surface to form a prefabricated slurry layer with a thickness of 5 mm, and maintain the coating coverage rate not less than 98%;

[0084] 3) The workpiece with the prefabricated slurry layer was naturally air-dried for 48 hours and cured at 450°C for 48 hours. The cured workpiece was placed under Ar for laser cladding treatment with a laser power of 2.8 kW, a scanning rate of 40 mm / s, a spot diameter of 4 mm, a workpiece rotation speed of 4 r / min, and an Ar gas flow rate of 15 L / min. After completion, the workpiece was cooled to room temperature and the residue on the surface of the workpiece was washed with a high-pressure airflow to clean the residue, thereby forming an aluminide-modified coating of this embodiment on the surface of the workpiece.

[0085] Example 9

[0086] 1) Based on the mass percentage of the solid phase cladding raw materials, 75% FeAl, 15% Al, 4% Pd, 4% Zr and 2% NH4Cl were weighed and placed in a planetary ball mill at 350 rpm for 24 hours, and passed through a 1000 mesh sieve to obtain a solid phase cladding powder;

[0087] Add 30% ethyl acetate compared to the weight of the solid phase cladding powder, stir thoroughly for 4 hours, and then place in a planetary ball mill at 400 rpm for 8 hours to obtain a uniformly mixed slurry, which is the cladding slurry;

[0088] 2) Use a high-pressure water gun to clean the workpiece surface for 5 minutes, rinse it with alcohol or acetone, and preheat the workpiece at 250°C for 60 minutes;

[0089] Spray the cladding slurry onto the workpiece surface to form a prefabricated slurry layer with a thickness of 5 mm, and maintain the coating coverage rate not less than 98%;

[0090] 3) The workpiece with the prefabricated slurry layer was naturally air-dried for 24 hours and cured at 450°C for 48 hours. The cured workpiece was placed under Ar for laser cladding treatment with a laser power of 2.8 kW, a scanning rate of 35 mm / s, a spot diameter of 4 mm, a workpiece rotation speed of 2 r / min, and an Ar gas flow rate of 18 L / min. After completion, the workpiece was cooled to room temperature and the residue on the surface of the workpiece was washed with a high-pressure airflow to clean the residue, thereby forming an aluminide-modified coating of this embodiment on the surface of the workpiece.

[0091] The thickness and anti-oxidation performance of the aluminide modified coatings prepared in Examples 3 to 9 were tested, and the results are shown in Table 2.

[0092] Table 2

[0093]

[0094]

[0095] It can be seen from Table 2 that by adjusting the FeAl, Al content and the thickness of the slurry layer within a certain range, a cladding layer with excellent effect can be prepared, and a coating with the best antioxidant performance can be obtained by optimizing the raw material formula. Therefore, the laser cladding aluminide coating and the preparation method thereof in the present invention are suitable for austenitic steel and high-temperature alloy parts used in large-aspect ratio and various complex-shaped workpieces such as large boilers and oil and gas field transportation pipelines. It has strong practicality, high diffusion rate, excellent membrane-base bonding, and excellent industrial mass production benefits.

[0096] Comparative Example 1

[0097] The difference between this comparative example and Example 1 is that FeAl is omitted, and the remaining steps and processes are all referred to Example 1 to obtain the aluminide modified coating of this comparative example.

[0098] Comparative Example 2

[0099] The difference between this comparative example and Example 1 is that Al is omitted, and the remaining steps and processes are all referred to Example 1 to obtain the modified coating of this comparative example.

[0100] Comparative Example 3

[0101] The difference between this comparative example and Example 1 is that Pd is omitted, and the remaining steps and processes are all referred to Example 1 to obtain the aluminide modified coating of this comparative example.

[0102] Comparative Example 4

[0103] The difference between this comparative example and Example 1 is that Zr is omitted, and the remaining steps and processes are all referred to Example 1 to obtain the aluminide modified coating of this comparative example.

[0104] Comparative Example 5

[0105] The difference between this comparative example and Example 1 is that NH4Cl is omitted, and the remaining steps and processes are referred to Example 1 to obtain the aluminide modified coating of this comparative example.

[0106] The thickness of the diffusion layer and the anti-oxidation performance of the samples obtained in Comparative Examples 1 to 5 were measured and compared with those in Example 1. The results are shown in Table 3.

[0107] Table 3

[0108]

[0109] It can be seen from Table 3 that any one of FeAl, Al, Pd, Zr and NH4Cl in the formula of the present invention has a significant effect on the antioxidant properties of the obtained coating, and only under the formula system of the present invention can a cladding layer with excellent effect be obtained.

[0110] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing an aluminide modified coating based on laser cladding, characterized in that: include, The solid phase cladding raw materials are ball milled and mixed to obtain solid phase cladding powder; The solid phase cladding powder and the liquid phase binder are stirred and ball-milled to obtain a cladding slurry; The cladding slurry is evenly sprayed onto the surface of the preheated workpiece to form a prefabricated slurry layer; The dried and solidified workpiece is placed in an inert atmosphere for laser cladding treatment, cooled after treatment, and the residue is cleaned to form an aluminide modified coating on the surface of the workpiece; Wherein, the solid phase cladding powder comprises, in terms of mass percentage, 60-80% FeAl, 10-30% Al, 3-6% Pd, 3-6% Zr and 2-7% NH4Cl.

2. The method for preparing an aluminide modified coating based on laser cladding according to claim 1, characterized in that: The mixing ball milling speed of the solid phase cladding raw material is 350-400 rpm and the time is 12-24 hours.

3. The method for preparing an aluminide modified coating based on laser cladding according to claim 1, characterized in that: The liquid phase binder is ethyl acetate, and the amount used is 10wt% to 30wt% of the solid phase cladding powder.

4. The method for preparing an aluminide modified coating based on laser cladding according to claim 1, characterized in that: The solid-phase cladding powder and the liquid-phase binder are stirred for 2 to 4 hours, and the ball milling speed is 350 to 400 rpm for 8 to 12 hours.

5. The method for preparing an aluminide modified coating based on laser cladding according to claim 1, characterized in that: The preheating treatment is medium frequency preheating at 200-250° C. for 30-60 minutes.

6. The method for preparing an aluminide modified coating based on laser cladding according to claim 1, characterized in that: The thickness of the prefabricated slurry layer is 1-5 mm, and the coating coverage is not less than 98%.

7. The method for preparing an aluminide modified coating based on laser cladding according to claim 1, characterized in that: The drying is carried out by natural air drying, and the drying time is 24 to 48 hours.

8. The method for preparing an aluminide modified coating based on laser cladding according to claim 1, characterized in that: The curing is performed at 300 to 450° C. for 24 to 48 hours.

9. The method for preparing an aluminide modified coating based on laser cladding according to claim 1, characterized in that: The cladding laser power of the laser cladding process is 2-2.8KW, the scanning rate is 20-40mm / s, the spot diameter is 3-5mm, the workpiece rotation speed is 3-6r / min, and the Ar gas flow rate is 15-20L / min.

10. The aluminide modified coating prepared by the preparation method according to any one of claims 1 to 9.